DNA methylation signature of chronic low-grade inflammation and its role in cardio-respiratory diseases - Matthias Wielscher; Pooja R. Mandaviya; Brigitte Kuehnel; Roby Joehanes; Rima Mustafa; Oliver Robinson; Yan Zhang; Barbara Bodinier; Esther Walton; Pashupati P. Mishra; Pascal Schlosser; Rory Wilson; et al. (Nature Communications, 2022)
Chronic inflammation, marked by C-reactive protein, has been associated with changes in methylation, but the causal relationship is unclear. Here, the authors perform a Epigenome-wide association meta-analysis for C-reactive protein levels and find that these methylation changes are likely the consequence of inflammation and could contribute to disease.